Reliability of accelerometry to assess impact loads of jumping and landing tasks - Simons, C.; Bradshaw, E. J. (Sports Biomechanics, 2016)
Overuse injuries, resulting from repetitive subacute impact loading, are a problem in high-performance sports. Monitoring of impact loading may aid in the prevention of these injuries. The current study aimed to establish the intra-day and inter-day reliability of a tri-axial accelerometer to assess impact loading during jumping and landing tasks. Twelve participants wore an accelerometer on their upper and lower back. They performed a continuous hopping task as well as drop landings and rebound jumps from three drop heights (37.5, 57.5 and 77.5 cm), peak resultant acceleration (PRA) was calculated for all tasks. The tasks were performed twice, one week apart at the same time of day. The difference in the mean, intra-class correlation coefficient, coefficient of variation and Cohens effect size were calculated as measures of reliability. PRA showed good intra-day reliability for the hopping task. Inter-day reliability of the PRA was moderate to good across all tasks. Reliability of PRA was slightly higher when accelerations were recorded on the lower back compared to the upper back. To assess impact loading, during continuous hopping, drop landings and rebound jumps, PRA recorded at both the upper and lower back appears to be a reliable measure.